The Effect of the Rme (Realistic Mathematics Education) Model on Reducing Mathematics Anxiety and the Ability to Operate Fractions in Grade 5 Elementary School Students - Fitriko, Fitriko (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to examine the effectiveness of the Realistic Mathematics Education (RME) learning model in reducing mathematics anxiety and improving fraction operation skills among fifth-grade elementary school students. Using an experimental research design with control and experimental groups, each consisting of 17 students, this study implemented the RME model in the experimental group while the control group received conventional learning. Hypothesis testing results using independent sample t-tests showed no significant differences in the pretest of both variables (p 0.05), but there were highly significant differences in the posttest of mathematics anxiety (p = 0.000) and fraction operation skills (p = 0.005). These findings prove that the RME learning model is effective in reducing mathematics anxiety and improving fraction operation skills among fifth-grade elementary school students, indicating that a realistic and contextual learning approach can be an effective alternative to improve the quality of mathematics instruction in elementary schools.